EFEKTIFITAS PEMANFAATAN GETAH BUNGA KAMBOJA UNTUK MENGHILANGKAN SAKIT GIGI DI MASA PANDEMI COVID-19 - I Made Budi Artawa; Ni Made Sirat; Ni Nyoman Dewi Supariani (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Toothache is an acute pain condition that requires immediate treatment. One of the herbal ingredients to treat toothache is frangipani flower sap because it is believed to contain anti-pain compounds such as alkaloids, tannins, flavonoids and tritepenoids which also function as antibiotics. Scientific evidence regarding the safety and effectiveness of using frangipani flower sap must be known so that the author is interested in writing